Non-iridium-based electrocatalyst for durable acidic oxygen evolution reaction in proton exchange membrane water electrolysis - Wu, Zhen-Yu; Chen, Feng-Yang; Li, Boyang; Yu, Shen-Wei; Finfrock, Y. Zou; Meira, Debora Motta; Yan, Qiang-Qiang; Zhu, Peng; Chen, Ming-Xi; Song, Tian-Wei; Yin, Zhouyang; Liang, Hai-Wei; et al. (Nature materials, 2023)
Iridium-based electrocatalysts remain the only practical anode catalysts for proton exchange membrane (PEM) water electrolysis, due to their excellent stability under acidic oxygen evolution reaction (OER), but are greatly limited by their high cost and low reserves. Here, we report a nickel-stabilized, ruthenium dioxide (Ni-RuO 2 ) catalyst, a promising alternative to iridium, with high activity and durability in acidic OER for PEM water electrolysis. While pristine RuO 2 showed poor acidic OER stability and degraded within a short period of continuous operation, the incorporation of Ni greatly stabilized the RuO 2 lattice and extended its durability by more than one order of magnitude. When applied to the anode of a PEM water electrolyser, our Ni-RuO 2 catalyst demonstrated >1,000 h stability under a water-splitting current of 200 mA cm −2 , suggesting potential for practical applications. Density functional theory studies, coupled with operando differential electrochemical mass spectroscopy analysis, confirmed the adsorbate-evolving mechanism on Ni-RuO 2 , as well as the critical role of Ni dopants in stabilization of surface Ru and subsurface oxygen for improved OER durability. Iridium-based electrocatalysts are traditional anode catalysts for proton exchange membrane water electrolysis but suffer from high cost and low reserves. An alternative, nickel-stabilized ruthenium dioxide catalyst with high activity and durability in acidic oxygen evolution reaction for water electrolysis is reported.